The Dissolution of the Austro-Hungarian Empire : Lessons for Currency Reform - Spencer, Michael (IMF Working Papers; Working Paper ;, 1992)
This paper investigates the currency reforms undertaken subsequent to the dissolution of the Austro-Hungarian Empire in 1918. The reforms were motivated by the lack of coordination of monetary policy and the absence of a rule for sharing seigniorage. Because the Successor States' reforms were not carried out simultaneously, individuals could choose where to convert their crowns based on where their real value was greatest. The cross-border flows of notes was substantial, to the detriment of Hungary which was last to reform. The Austrian and Hungarian currencies were stabilized only with the help of League of Nations financial programs.